Increasing collaborative research output between early-career health researchers in Africa: lessons from the CARTA fellowship program - Dieudonne Uwizeye; Florah Karimi; Emmanuel Otukpa; Moses W. Ngware; Hesborn Wao; Jude Ofuzinim Igumbor; Sharon Fonn (Taylor & Francis Group, 2020)
In 2008 nine African Universities and four African research institutions, in partnership with non-African institutions started the Consortium for Advanced Research Training in Africa (CARTA) to strengthen doctoral training and research capacity on health in Africa. This study describes particular aspects of the CARTA program that promotes collaboration between the PhD fellows in the program, and determines the patterns of collaborative publications that resulted from the intervention. We reviewed program monitoring and evaluation documents and conducted a bibliometric analysis of 806 peer-reviewed publications by CARTA fellows published between 2011 and 2018. Results indicate that recruiting multidisciplinary fellows from various institutions, encouraging registration of doctoral-level fellows outside home institutions, and organizing joint research seminars stimulated collaborative research on health-related topics. Fellows collaborated among themselves and with non-CARTA researchers. Fellows co-authored 75 papers (10%) between themselves, of which 53 (71%) and 42 (56%) included fellows of different cohorts and different disciplines respectively, and 19 (25%) involved fellows of different institutions. CARTA graduates continued to publish with each other after graduating - 11% of the collaborative publications occurred post-graduation - indicating that the collaborative approach was maintained after exiting from the program. However, not all fellows contributed to publishing collaborative papers. The study recommends concerted effort towards enhancing collaborative publications among the CARTA fellows, both doctoral and post-doctoral, which can include holding research exchange forums and collaborative grant-writing workshops.